DEVELOPMENT TRENDS AND PROBLEMS OF RENEWABLE (ALTERNATIVE) ENERGY SOURCES IN KYRGYZSTAN - N.A, Murzakulov; Gulzar, Tajibaeva; Tsyuyxuey, Sya; Maksatbek, Nazaev (Research Focus International Scientific Journal, 2026)
This article examines the challenges facing Kyrgyzstan’s energy system and the key factors contributing to these problems. It identifies significant potential for improving the efficiency of renewable energy sources and reducing the cost of heat and electricity, offering broad prospects for addressing energy and environmental challenges in the future.